Prevalence of low back pain and associated risk factors among car mechanics in Malacca, Malaysia - Tan, Zhong Shern; Ambusam, Subramaniam; Vinosh Kumar, Purushothaman (INTI International University, 2020)
Background: Work-related low back disorder is one the common musculoskeletal disorders that has been concurrently associated with the work characteristic and position during work. The working posture of car mechanics that involves high force exertion, vibration, prolonged standing and awkward working position has directly contributed to the development of low back pain. Although previous study has addressed on this issue, there is a paucity of information in regards to the prevalence, risk factors of low back pain and the association between these two variables. Thus, the current study was conducted to address this issue with following objective: Objective: 1. To determine the prevalence and the risk factors of work-related low back pain among car mechanics in Malacca City, Melaka, Malaysia. 2. To examine the association between low back pain and risk factors of work-related low back pain among car mechanics in Malacca City, Melaka, Malaysia. Materials & Methodology: This cross-sectional study includes 120 car mechanics selected from 43 car workshops in Malacca city by simple random sampling method. Musculoskeletal disorders and disability data was gathered by using standardized Nordic self-report questionnaire and Oswestry disability index. Descriptive statistics were present for all categorical variables. Chi-Square were used to determine the association between low back pain and the related risk factors. Results: The findings of the current study showed that 80.0% of car mechanics experienced low back disorder in Malacca city. The risk factors such as BMI, rest time/rest period and squatting for long period showed a significant association with low back trouble. Conclusion: The inappropriate working posture and contributing risk factors has led to steady increase of low back pain among car mechanics. An early education of healthy lifestyle involving exercise and good diet as well as practice of effective ergonomics intervention should be encouraged among them in order to prevent further injury and eliminate low back pain.